2012
DOI: 10.1111/j.1745-4603.2011.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Extensograph Properties of Wheat‐flour Dough: Artificial Neural Networks and a Genetic Algorithm Approach

Abstract: Wheat‐flour dough is a viscoelastic material with nonlinear rheological behavior. Extensograph is a useful system for dough rheological measurement. Our purpose in this research was to apply soft computation tools for predicting the extensograph properties of dough from several physicochemical properties of flour. This study used the resulting model to suggest modifications of processing conditions for reducing economic loss and minimizing product quality deterioration. A generalized feed‐forward artificial ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
1
9
1
2
Order By: Relevance
“…It was found that both R max and extensibility increased with protein levels for frozen dough, and this is in agreement with results reported by other researchers (Abbasi et al 2012;Faegestad et al 2000;Lin et al 2003;Uthayakumaran et al 1999). Using flours with protein contents of 10-13 %, Abbasi et al (2012) showed a positive correlation between protein content and extensibility, and between protein content and resistance to extension, with correlation coefficients of 0.4 and 0.3, respectively.…”
Section: Impacts Of Flour Protein Content On Dough Rheologysupporting
confidence: 93%
See 1 more Smart Citation
“…It was found that both R max and extensibility increased with protein levels for frozen dough, and this is in agreement with results reported by other researchers (Abbasi et al 2012;Faegestad et al 2000;Lin et al 2003;Uthayakumaran et al 1999). Using flours with protein contents of 10-13 %, Abbasi et al (2012) showed a positive correlation between protein content and extensibility, and between protein content and resistance to extension, with correlation coefficients of 0.4 and 0.3, respectively.…”
Section: Impacts Of Flour Protein Content On Dough Rheologysupporting
confidence: 93%
“…Using flours with protein contents of 10-13 %, Abbasi et al (2012) showed a positive correlation between protein content and extensibility, and between protein content and resistance to extension, with correlation coefficients of 0.4 and 0.3, respectively. Those cited studies above were done on fresh dough, and thus, the results of this study provided evidence that frozen dough maintained similar relationships between extensional rheological properties and protein content as compared to fresh dough.…”
Section: Impacts Of Flour Protein Content On Dough Rheologymentioning
confidence: 88%
“…ANNs have been used in prediction of some parameters in various processes (Alvarez, 2009;Chakraborty & Shrivastava, 2019;Kashaninejad, Dehghani, & Kashiri, 2009;Koji c et al, 2019;Lamrini, Della Valle, Trelea, Perrot, & Trystram, 2012;Sablani, Baik, & Marcotte, 2002) and food quality evaluation (Broyart & Trystram, 2003;Funes et al, 2015;Goyache et al, 2001) or to predict dough rheological properties (farinograph peak, extensibility, and maximum resistance) from the torque developed during mixing (Ruan, Almaer, & Zhang, 1995). Other studies revealed that ANNs were used to predict the parameters of farinograph (Abbasi, Emam-Djomeh, & Seyedin, 2011), extensograph, alveograph, and fundamental rheological properties of dough from several physicochemical properties of flour (Abbasi et al, 2012;Abbasi, Emam-Djomeh, & Ardabili, 2014;Abbasi & Mohammadifar, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Farinograph and extensograph are the most common empirical evaluation equipment to indicate the development of the dough during mixing (Ktenioudaki et al, 2011), which have been widely used in the evaluation of processing performance of bread, steamed bread, noodles, and other products. And there is a certain correlation between the indexes measured by the two instruments (Abbasi et al, 2012; Huang et al, 2010; Miś et al, 2012).…”
Section: Introductionmentioning
confidence: 99%